Excursion business in the context of sustainable tourism development - Liudmyla Hutsal (Journal of Education, Health and Sport)
The article examines the role of excursion activities in the development of sustainable tourism as an important area of the modern tourism industry. Sustainable tourism, which is guided by the principles of environmental responsibility, social inclusion and economic sustainability, is aimed at preserving natural and cultural resources and ensuring the long-term development of local communities. Excursion business, as one of the main components of tourism services, has a significant potential for implementing sustainable tourism ideas due to the possibility of direct influence on the minds of tourists, promotion of cultural heritage and support for the local economy.